Comparison of Gamma Irradiated and Raw Lignite in Bioliquefaction Process by Fungus T5 - I. Sugoro; D.I. Astuti; D. Sasongko; P. Aditiawati (Atom Indonesia, 2012)
The bioliquefaction of coal is a processing technology for converting solid coal to liquid oil at ambient temperature by helping microorganism. The pretreated of lignite is important to decrease the hydrofobic of lignite surface. One of pretreated method was irradiation by gamma rays. Aim of this research was to compare the gamma irradiated lignite and raw lignite in bioliquefaction process by selected fungus T5. The fungus was identified by molecular method using 18S rDNA. Treatments were A (MSS + gamma irradiated lignite 5% + T5) and B (MSS + raw lignite 5% + T5) and culture type was sub-merged. The parameters observed were colonization, bacterial and fungal enumeration, identify of dominant bacteria using 16S rDNA and characterization of bioliquefaction product by UV-Vis spectroscopy dan gas chromatography – mass spectrometry (GCMS). The results showed that fungus T5 belongs to Ascomycota, Trichoderma asperellum. Fungus has the ability to growth and liquefy gamma irradiated and raw lignite. Bacteria were detected in raw lignite treatment and dominant bacteria were identified as Bacillus megaterium and Bacillus thuringensis. UV-Vis analysis showed that boliquefaction product mainly contained naphtacene, naphthalene, and anthracene for gamma irradiated lignite, but anthracene and benzene for raw lignite. For GCMS analysis, 22 and 38 compounds were identified for gamma irradiated and raw lignite. Both treatment had different number of hydrocarbon, i.e. C6 – C35 (A) and C10 – C35 (B) and dominated by aromatic acids, aliphatic and phenylethers. Percent area of gasoline (C7 – C11) and diesel (C10 – C24) fractions on the treatment B was 7.23% and 62.35%, while in treatment A was 7.22% and 44.27%. Based on the results, pretreated of lignite by gamma irradiation could be increased the bioliquefaction product.Received: 5 December 2011; Revised: 21 May 2012; Accepted: 11 June 2012